TRANSPORTATION ACCESS AND DELAY IN DIAGNOSIS FOR PEDIATRIC INFLAMMATORY BOWEL DISEASE PATIENTS. (22nd January 2022) - Zeky, Nicole; LeBlanc, Colleen; McDonough, Elizabeth; Moulton, Dedrick
Abstract: PURPOSE: Inflammatory bowel disease (IBD), consisting of both Crohn's Disease (CD) and ulcerative colitis (UC), affects nearly 80, 000 children in the United States. African American patients have more perirectal phenotype which might indicate more severe disease activity however it is unclear why. There is no published data on transportation access and how it relates to pediatric IBD. The purpose of this study is to compare pediatric IBD patients with low access to care to those with more access to care and their severity of disease at diagnosis. Our hypothesis is that those patients who live farther from the children's hospital and bus stops will have more of a lag time in their diagnosis as defined by two or more visits with another provider for complaints concerning for IBD compared to those patients with more ease of access to care. We aim to assess the impact of proximity to care facilities, bus stops and primary children's hospital and disease severity at the time of diagnosis for pediatric IBD population. METHODS: This study is a retrospective chart review of patients seen by the Louisiana State University Health Science Center Pediatric Gastroenterology division at Children's Hospital New Orleans from 2019 until 2021. A list of patients with the diagnosis of either CD or UC after 2019 was generated. Both qualitative and quantitative data was collected. Patient's addresses were used to determine the distance to their primary gastroenterologist clinic. Data collected also included their proximity location to bus stops, number of visits prior to diagnosis of IBD. RESULTS: There were 71 pediatric patients diagnosed during the study period. The patients were predominantly male (51%) and white (65%) with average age at diagnosis of 12 years old (± 3.3 years). Forty-eight (68%) patients were diagnosed with CD. More Crohn's Disease patients had 2 or more visits before diagnosis compared to those with UC (48% versus 30%). The average distance for African American patients to the children's hospital was 50.5 miles (± 55.9 miles) which was similar to the white patients (53.0 ± 59.8 miles). Of the 23 African American patients included in the study 14 (61%) had at least 2 visits before being diagnosed with IBD. In comparison, 15 of the 46 (33%) white patients had at least 2 visits before receiving a diagnosis of IBD. Most patients had a pediatrician listed as their primary care provider for both African American and white patients (70% versus 80%). CONCLUSION: The significance of a delay in diagnosis and pediatric IBD is unclear, however further studies to determine if less access of care is predictive of greater disease severity and activity at presentation may be warranted. Additional studies will be completed to determine the relationship between proximity to bus stops and disease burden at diagnosis.